Influence of Morphine on Pericyte-Endothelial Interaction: Implications for Antiangiogenic Therapy. (16th January 2012) - Luk, Kathryn; Boatman, Sonja; Johnson, Katherine N.; Dudek, Olivia A.; Ristau, Natalie; Vang, Derek; Nguyen, Julia; Gupta, Kalpna
Abstract : Morphine stimulates tumor angiogenesis and cancer progression in mice. We examined if morphine influences endothelial-pericyte interaction via platelet-derived growth factor-BB (PDGF-BB) and PDGF receptor-β (PDGFR-β ). Clinically relevant doses of morphine stimulated PDGF-BB secretion from human umbilical vein endothelial cells and activated PDGFR-β and mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) phosphorylation in human pericytes. These in vitro effects of morphine were translated into promotion of tumor angiogenesis in a transgenic mice model of breast cancer when treated with clinically used dose of morphine. Increased vessel-associated immunoreactivity of desmin and PDGFR-β was observed on pericytes in tumors of morphine-treated mice. These data suggest that morphine potentiates endothelial-pericyte interaction via PDGF-BB/PDGFR-β signaling and promotes tumor angiogenesis, pericyte recruitment, and coverage of tumor vessels. We speculate that morphine may impair the effectiveness of antiangiogenic therapy by influencing vascular pericyte coverage.